OC-086 The Characteristics of Ileo-Colonic Neuroendocrine Tumours Identified in the UK Bowel Cancer Screening Programme (BCSP)?. (17th August 2016) - Basuroy, R; O'Donnell, K; Brooks, C; Srirajaskanthan, R; Ramage, J
Abstract : Introduction: Neuroendocrine tumours (NETs) identified during BCSP, in particular rectal NETs, are reported to be smaller and earlier stage than those identified otherwise. There is no published data on the characteristics of NETs identified as part of the UK BCSP. Methods: Data requests were made to UK BCSP and NET related queries were run which identified 146 patients between 2005–14. Written requests to individual BCSP practitioners to complete a proforma about endoscopy, histology, and secondary therapy assesments (including supplemental anonymised reports). Results: 102 written proformas were returned for analysis with sites, sizes and grades outlined below. Colorectal cancer was identified as a co-malignancy in 7% of patients with NETs. Conclusion: 50% of NETs identified are rectal NETs which are invariably small (<10mm), low grade and early stage. 27% of NETs identified are small bowel NETS that can have invasive, nodal and metastatic disease. The results corroborate findings of early disease in rectal NETs but additionally informs on advanced disease in NETs from other primary sites. Disclosure of Interest: None Declared